Delayed spontaneous perforation of polyvinyl alcohol membrane—Covered atrial septal defect closure devices. Issue 4 (18th August 2016) - Labombarda, Fabien; Roule, Vincent; Beygui, Farzin
Abstract : Percutaneous device closure has become the first choice for secundum atrial septal defect (ASD) closure when feasible in case of favorable anatomy. The Ultrasept II ASD occluder® device (Cardia Inc, Eagan, MN) is made of two nitinol disc frames covered with polyvinyl alcohol membranes, a synthetic polymer with a large application in the biomedical field. Four relatively early malfunctions of the polyvinyl alcohol membrane were observed in a series of six consecutive patients treated with ASD Ultrasept II closure device in our institution. Operators have to be aware of this apparently rare complication that is likely to be underestimated, associated with such devices. © 2016 Wiley Periodicals, Inc.